Analisis Cost-Benefit dan Value for Money Aplikasi Akuntansi Digital terhadap Kinerja Keuangan Usaha Mikro, Kecil, dan Menengah di Kalimantan Selatan - Nashoha, Muhammad Rizalun (Sharia Journal and Education Center Publishing, 2025)
The adoption of financial technology is crucial for the sustainability of Micro, Small, and Medium Enterprises (MSMEs), but doubts regarding cost efficiency and the tangible benefits of technology investment remain a major obstacle for businesses in the region. This study aims to evaluate the feasibility of implementing digital accounting applications through quantitative Cost-Benefit analysis and Value for Money (VfM) assessment, as well as to analyze its impact on improving the financial performance of MSMEs in South Kalimantan. This study uses quantitative methods with data collection techniques through questionnaire surveys of 67 MSME players who have used digital accounting applications. Data analysis was conducted by calculating the Benefit-Cost Ratio (BCR) and VfM indicators, which include Economic, Efficiency, and Effectiveness aspects. The results show that the implementation of digital accounting applications produces a BCR value [specify the number, e.g., >1], indicating that the economic benefits received exceed the investment costs incurred. Based on the Value for Money assessment, the use of the application was proven to meet economic criteria in procurement, be efficient in operational processes, and be effective in producing accurate financial reports. Overall, the implementation of this system had a positive and significant impact on improving the financial performance of MSMEs through operational cost efficiency and speed of managerial decision-making.